(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article gives information about linguistic aspects of modality components in English and Uzbek languages. It studies the transfer of modality and translation methods of English modal verbs into Uzbek language. The article discusses the features of the translation of modal verbs from English into Uzbek, as well as the special use of phrasal units in a modal meaning. It highlights the problem of transferring the category of modality when translating from English language. To solve the problem, methods of transferring the modality are considered. Some peculiarities of translation of modal verbs and basic concept of modality are analysed.